Debts and Receivables in the Qur'an: A Ma'na-cum-Maghza Interpretation of Q.S. Al-Baqarah [2]: 282 - Amalia, Rosyida; Masrury, Farhan; Wahyu Sejati, Sartika Dita; Budi, Eko Prasetyo; Abidin, Ahmad Zainal (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2026)
This paper aims to analyze the historical meaning and explore the significance of Q.S. al-Baqarah [2]: 282 from the perspective of tafsir mu‘āmalah using the ma‘nā cum maghzā approach. This verse is related to debt transactions (mudāyanah), which in the early period of Islam often led to potential injustice due to the absence of clear transaction records and the prevalence of usurious practices that disadvantaged borrowers. This study employs a qualitative method with a contextual exegesis approach through the analysis of historical meaning (ma‘nā al-tārīkhī) and the exploration of the main message of the verse (maghzā). The data were collected through library research by examining various classical and contemporary Qur’anic commentaries relevant to the study of mu‘āmalah. The results of the study show that Q.S. al-Baqarah [2]: 282 emphasizes three main principles in economic transactions: the recording of transactions as a form of legal certainty, the presence of a just scribe to maintain the objectivity of the agreement, and witnesses as a mechanism for transaction verification. These principles function to ensure justice, transparency, and the protection of rights in economic relations. In a contemporary context, the message of this verse is relevant to modern economic administrative practices such as written contracts, accounting systems, and transaction regulations in Islamic financial institutions. Thus, Q.S. al-Baqarah [2]: 282 can be understood as a normative foundation for building a fair, transparent, and accountable system of mu‘āmalah in modern economic life. Tulisan ini bertujuan untuk menganalisis makna historis serta mengungkap signifikansi QS. al-Baqarah [2]: 282 dalam perspektif tafsir muamalah melalui pendekatan ma‘nā cum maghzā. Ayat ini berkaitan dengan praktik utang-piutang (mudāyanah) yang pada masa awal Islam sering menimbulkan potensi ketidakadilan akibat tidak adanya sistem pencatatan transaksi yang jelas serta praktik riba yang merugikan pihak peminjam. Penelitian ini menggunakan metode kualitatif dengan pendekatan tafsir kontekstual melalui analisis makna historis (ma‘nā al-tārīkhī) dan penggalian pesan utama ayat (maghzā). Data penelitian diperoleh melalui studi kepustakaan dengan menelaah berbagai literatur tafsir klasik dan kontemporer yang berkaitan dengan kajian muamalah. Hasil penelitian menunjukkan bahwa QS. al-Baqarah [2]: 282 menekankan tiga prinsip utama dalam transaksi ekonomi, yaitu pencatatan transaksi sebagai bentuk kepastian hukum, kehadiran penulis yang adil untuk menjaga objektivitas perjanjian, serta kesaksian sebagai mekanisme verifikasi transaksi. Ketiga prinsip tersebut berfungsi untuk menjaga keadilan, transparansi, dan perlindungan hak dalam hubungan ekonomi. Dalam konteks kontemporer, pesan ayat ini relevan dengan praktik administrasi ekonomi modern seperti kontrak tertulis, sistem akuntansi, serta regulasi transaksi dalam lembaga keuangan syariah. Dengan demikian, QS. al-Baqarah [2]: 282 dapat dipahami sebagai landasan normatif dalam membangun sistem muamalah yang adil, transparan, dan akuntabel dalam kehidupan ekonomi modern.